Abaca naman fostering agro-industrial and economic growth through an inclusive and sustainable abaca processing facility - Garchitorena, Carla Y.; Luna, Markel Cesar A. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Source of the Fiber internationally known as Manila Hemp, the abaca plant is indigenous to the Philippines whose climatic condition and volcanic soils make it favorable for its cultivation. Its primary processing begins with the abaca fiber being extracted from the stalk of the plant, specifically from the outer covering of the leaf sheath through a laborious process which involves many operations such as tuxying, stripping, drying, and final processing. Despite all these advantages, low farm productivity and inconsistent fiber quality, mainly attributed to a fragmented industry enduring from lack of post-harvest and processing facilities amongst other issues, continue to hamper the Philippine Abaca Industry from optimizing its potential. Giving rise to Abaca naman, and abaca agro-industrial processing facility. This centralized facility is comprised of five individual buildings brought together by its customized abaca panels that symbolizes the process that abaca undergoes in post-harvest all working together in bringing improvement and development in the Abaca Industry at the regional and eventually, national level.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Abaca plant trade; Abaca agro-industrial processing facility